DIGITAL MARKETTING AS A PROMOTIONAL MEDIUM IN IMPROVING THE CREATIVE ECONOMY OF MSMES - Hartatik Hartatik (International Journal of Engagement and Empowerment, 2022)
Program this service activity is aimed at introducing the district and its village potential including history, culture, and natural potential such as mountains, regional arts, culinary. The natural resources in the village can support the potential to be raised and developed into tourism. No matter how big the tourism potential is, if it is not supported by qualified promotional and marketing tools, it will not develop rapidly. The amount of operational costs is sometimes not proportional to income due to the small number of tourists who visit. In the tourism village until now due to the lack of utilizing information technology to disseminate the tourism potential of the village. Therefore, in this community partnership program, assistance and implementation of training on the use of information technology as a promotional medium is carried out in improving the creative economy